The heart rate frequency of active individuals is lower than sedentary individuals during anaerobic physical activity (study on males 18-24 years old) - Kukuh Pambuka Putra; Venti Agustina; Muchamad Arif Al Ardha; Juan Prince Enid Zebua (Journal Of Sport Education (JOPE), 2023)
(English)Currently, in the field of sports and health it is believed that individuals who are active in physical activity or exercise regularly have a lower heart rate compared to sedentary individuals, both at rest and during physical activity. The heart rate reflects the intensity of a person's physical activity. This study aims to prove differences in heart rate frequency in active individuals and sedentary individuals when performing anaerobic physical activities. The subjects of this study were 16 active men and 16 sedentary men aged 18-24 years. This study used an experimental method with treatment in the form of anaerobic physical activity, namely push-ups, sit-ups and squats sequentially and monitoring the heart rate was recorded every 10 seconds. The results showed that the active group had a lower heart rate compared to the sedentary group when doing anaerobic physical activity. The conclusion of this study is that when doing the same anaerobic physical activity, for active individuals the increase in physical activity intensity that occurs is not as great as that experienced by sedentary individuals. (Indonesian)Saat ini, dalam bidang olahraga dan kesehatan diyakini bahwa individu yang aktif beraktivitas fisik atau rutin berolahraga memiliki frekuensi denyut jantung yang lebih rendah dibandingkan dengan individu sedenter, baik ketika istirahat maupun ketika beraktivitas fisik. Frekuensi denyut jantung mencerminkan intensitas aktivitas fisik yang dilakukan seseorang. Penelitian ini bertujuan untuk membuktikan perbedaan frekuensi denyut jantung pada individu aktif dan individu sedenter ketika melakukan aktivitas fisik anaerobik. Subyek penelitian ini adalah 16 orang laki-laki aktif dan 16 orang laki-laki sedenter berusia 18-24 tahun. Penelitian ini menggunakan metode eksperimen dengan perlakuan berupa aktivitas fisik anaerobik yaitu push-up, sit-up dan squat secara berurutan serta dilakukan pemantauan frekuensi denyut jantung yang dicatat setiap 10 detik. Hasil menunjukkan bahwa kelompok aktif memiliki frekuensi denyut jantung lebih rendah dibandingkan dengan kelompok sedenter ketika beraktivitas fisik anaerobik. Kesimpulan dari penelitian ini adalah bahwa ketika melakukan aktivitas fisik anaerobik yang sama, bagi individu aktif kenaikan intensitas aktivitas fisik yang terjadi tidak sebesar yang dialami oleh individu sedenter.   Copyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.